Ampithoidae (Crustacea: Amphipoda) from the Persian Gulf and the Gulf of Oman - Momtazi, Farzaneh (Zootaxa, 2022)
The previous studies of amphipods in the Persian Gulf and the Gulf of Oman recorded 8 species of the family Ampithoidae Boeck, 1871. In the present study Cymadusa makranica sp. nov. is described and Plumithoe madagascariensis Myers, 2012 is recorded for the first time from the region. The new species is characterized by the shape of gnathopods and setation on the inner plate of first maxilla and uropods. The detailed drawings of Cymadusa filosa Savigny, 1816 and C. setosa (Haswell, 1879) materials are provided.